Legalitas Kontrak Perjanjian Kredit Motor Tanpa Akta Otentik Notaris oleh Kreditur Di Indonesia - Agung Sudjadi; Yuniar Rahmatiar; Muhamad Abas; Suyono Sanjaya (JURNAL HUKUM PELITA, 2025)
The purpose of this study is to establish legal certainty regarding the validity of contracts and the legitimacy of execution by creditors in motor vehicle financing agreements that are not formalized through notarial deeds and court rulings, as well as to assess their impact on legal certainty and debtor protection. This research employs a normative legal method by collecting data through a literature review of legislation, court decisions, legal literature, and relevant motor vehicle financing contracts. The study finds that motor vehicle financing contracts without notarial deeds have weaknesses in evidentiary strength, creating opportunities for creditors in Indonesia to execute collateral without court authorization. However, the legality of such execution must be based on Constitutional Court Decision No. 2/PUU-XIX/2021, which states that execution may proceed without a court ruling if there is voluntary surrender and a clear basis for execution. Thus, this research provides an original contribution by thoroughly examining the legal aspects of fiduciary guarantee execution in the context of motor vehicle financing contracts, a topic that has received little attention in non-bank financing practices in Indonesia